Triazolopyridine hybrids as bipolar host materials for green phosphorescent organic light-emitting diodes (OLEDs). (January 2019) - Vadagaonkar, Kamlesh S.; Yang, Chia-Jung; Zeng, Wei-Hao; Chen, Jian-Hong; Patil, Bhausaheb N.; Chetti, Prabhakar; Chen, Li-Yin; Chaskar, Atul C.
Abstract: Four new bipolar host materials (TPA-1, CBZ-1, CBZ-2 and CBZ-3 ) comprising triphenylamine and carbazole as electron donors with hole-transporting properties and [1, 2, 4]triazolo[4, 3- a ]pyridine as an electron acceptor with electron-transporting property have been synthesized, characterized and applied as host materials for green phosphorescent OLEDs. Their thermal, photophysical, electrochemical and carrier-transport properties have also been studied. These bipolar host materials showed good thermal and morphological stabilities. These compounds efficiently suppress the intramolecular charge transfer between donor and acceptor and possess moderate triplet energies ( E T  = 2.48–2.51 eV). These materials exhibited good performances in green PhOLEDs and showed maximum external quantum efficiency in the range of 9.2–16.7%. A green-phosphorescent device incorporating CBZ-2 as the host doped with Ir(ppy)3 achieved a maximum external quantum efficiency, current efficiency, and power efficiency of 16.7%, 62.5 cd A −1, and 69.7 lm W −1, respectively. Graphical abstract: Image 1 Highlights: Four bipolar hosts comprising triphenylamine, carbazole as donors and triazolopyridine as an acceptor were synthesized. These bipolar host materials showed good thermal and morphological stabilities. These bipolar host materials exhibited triplet energies ranging from 2.48-2.51 eV. They displayed good external quantum efficiencies (9.2–16.7%) for green PhOLEDs with low efficiency roll-off.